A PRACTICAL APPROACH TO THE METHODOLOGY OF ESP TEACHING - Carmen D. CARAIMAN (Challenges of the Knowledge Society)
The ability to master specialized terminology in English plays an ever increasing role in the selection of candidates for employment due to the internalization of the labour market and of the research activity exchanges. Subsequent to Romania’s joining the EU, the vacancies available on the European labour market, including in the academic area, represent the major factor that has determined an increase in the interest paid in the acquisition of specialized terminology. This interest is shared by trainees, trainers, authors of textbooks and ESP (English for Specific Purposes) specialists. In the present paper, we intend to outline some of the main directions, methods and strategies that an ESP course should follow for providing high-quality and up-to-date information to the trainees interested in acquiring specialized vocabulary for their future workplaces. Finally, we intend to anticipate trends that the evolution of specialized foreign language teaching methodology will follow in the near future.